PO9 Road to Strengthening Research in Natural Products. View from the Technological University of Uruguay - Figliolo Mederos, María Rossina; Cardozo, Jhonatan; Estévez, Annabela (Revista Productos Naturales, 2025)
In Uruguay, where Montevideo concentrates much of the educational and scientific infrastructure, the expansion of areas such as natural products in institutions in the interior has been key to regional development. This is reflected in impactful projects, such as clinics, theses, and workshops, that explore various aspects of these products. These projects have allowed students and professionals to become involved in the research and development of new products, fostering knowledge exchange between different regions.